2015
DOI: 10.1093/rheumatology/kev251
|View full text |Cite
|
Sign up to set email alerts
|

Calprotectin more accurately discriminates the disease status of rheumatoid arthritis patients receiving tocilizumab than acute phase reactants

Abstract: Calprotectin serum levels seem to be an accurate biomarker for assessing disease activity in RA patients receiving TCZ.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
34
0
3

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 29 publications
(41 citation statements)
references
References 16 publications
4
34
0
3
Order By: Relevance
“…We recently demonstrated that calprotectin is a more accurate biomarker than CRP level or ESR for the assessment of disease activity in RA patients receiving tocilizumab, a biologic agent with a dramatic impact on APR due to its blocking of IL-6, which may lead to an overestimate of the rates of response when using composite indices that include the acute-phase response, such as the DAS or SDAI (26). Therefore, calprotectin emerges as a biomarker that more accurately stratifies disease activity than the APRs in RA patients receiving biologic therapy, irrespective of the mechanism of action (inhibition of TNF or IL-6).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…We recently demonstrated that calprotectin is a more accurate biomarker than CRP level or ESR for the assessment of disease activity in RA patients receiving tocilizumab, a biologic agent with a dramatic impact on APR due to its blocking of IL-6, which may lead to an overestimate of the rates of response when using composite indices that include the acute-phase response, such as the DAS or SDAI (26). Therefore, calprotectin emerges as a biomarker that more accurately stratifies disease activity than the APRs in RA patients receiving biologic therapy, irrespective of the mechanism of action (inhibition of TNF or IL-6).…”
Section: Discussionmentioning
confidence: 99%
“…Third, the cutoff point of calprotectin associated with remission or low disease activity in RA should be interpreted with caution and merits further investigation in studies with a larger sample size in order to establish the clinical significance. A higher cutoff of calprotectin levels was found in patients treated with tocilizumab (26). Fourth, the clinical value of calprotectin measurements in individual patients is hampered by some overlap values between patients with different degrees of disease activity.…”
mentioning
confidence: 98%
See 1 more Smart Citation
“…23 CLP correlates with inflammatory indices, including C-reactive protein (CRP), erythrocyte sedimentation rate (ESR), and serum amyloid A protein (SAA) and inversely with TNF-a inhibitors through levels. 74,76,77 CLP serum levels seem to perform even better compared to CRP and ESR. In fact, CLP has showed to correlate better with all clinical indices, such as 28 joint-disease activity score and simplified disease activity index.…”
Section: Clp In Rheumatic Diseasesmentioning
confidence: 95%
“…67 CLP serum levels correlate with disease activity and are associated with markers of more severe RA in many studies. 48,49,61,64,66,[68][69][70][71][72][73][74][75][76] CLP has been found to be higher in the serum of rheumatoid factor 48,49,69,70,71,73 and anticitrullinated peptide positive patients 23,49,64,72 compared with seronegative ones. 23 CLP correlates with inflammatory indices, including C-reactive protein (CRP), erythrocyte sedimentation rate (ESR), and serum amyloid A protein (SAA) and inversely with TNF-a inhibitors through levels.…”
Section: Clp In Rheumatic Diseasesmentioning
confidence: 99%